2022
DOI: 10.3322/caac.21732
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance status and cancer stage at diagnosis and survival in the United States

Abstract: Previous studies using data from the early 2000s demonstrated that patients who were uninsured were more likely to present with late‐stage disease and had worse short‐term survival after cancer diagnosis in the United States. In this report, the authors provide comprehensive data on the associations of health insurance coverage type with stage at diagnosis and long‐term survival in individuals aged 18–64 years who were diagnosed between 2010 and 2013 with 19 common cancers from the National Cancer Database, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Unlike most developed countries, the US does not have a universal health care system, and health insurance coverage is a strong determinant of health care access and health outcomes. [10][11][12] In the US, the federal Medicare program insures Americans 65 years or older and certain younger people with disabilities or specific conditions; most Americans younger than 65 years receive private health insurance through employers; and the federally aided, state-operated Medicaid program provides insurance coverage for low-income people, with income eligibility varying by state. 11 Although the Patient Protection and Affordable Care Act significantly expanded insurance coverage in the US in the last decade, approximately 30 million Americans lacked health insurance coverage in 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most developed countries, the US does not have a universal health care system, and health insurance coverage is a strong determinant of health care access and health outcomes. [10][11][12] In the US, the federal Medicare program insures Americans 65 years or older and certain younger people with disabilities or specific conditions; most Americans younger than 65 years receive private health insurance through employers; and the federally aided, state-operated Medicaid program provides insurance coverage for low-income people, with income eligibility varying by state. 11 Although the Patient Protection and Affordable Care Act significantly expanded insurance coverage in the US in the last decade, approximately 30 million Americans lacked health insurance coverage in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, estimates in the US have been limited to the Surveillance, Epidemiology, and End Results Program (SEER) registries from 13 states or fewer, and the studies were not able to examine the contribution of some factors that are unique within the US context to increased suicide risks, such as state of residence, insurance coverage, ethnicity, and county-level socioeconomic status. Unlike most developed countries, the US does not have a universal health care system, and health insurance coverage is a strong determinant of health care access and health outcomes . In the US, the federal Medicare program insures Americans 65 years or older and certain younger people with disabilities or specific conditions; most Americans younger than 65 years receive private health insurance through employers; and the federally aided, state-operated Medicaid program provides insurance coverage for low-income people, with income eligibility varying by state .…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve the noted inefficiencies and enrollment, it is recommended that future researchers include HbA1c testing with existing order sets for all newly diagnosed cancer patients entering the clinic and consider assessing and expanding eligibility criteria as appropriate. Also, decreased access to health care is associated with undiagnosed T2D, uncontrolled T2D, and cancer diagnosed at an advanced stage so it is imperative that underserved populations at increased risk of experiencing challenges accessing health care are included in future studies 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…Miller also cites a related study that her colleagues published in July 2022, which examined health insurance status and cancer stage at diagnosis and survival. 3 They found worse short-and long-term survival outcomes for patients without insurance for each stage for all cancers combined. When looking at specific cancers, they found that uninsured patients with stage I disease had worse survival rates than privately insured patients with stage II disease for six cancer types (prostate, colorectal, non-Hodgkin lymphoma, oral cavity, liver, and esophagus).…”
Section: Meeting the Needs Of Cancer Survivorsmentioning
confidence: 98%
“…Miller also cites a related study that her colleagues published in July 2022, which examined health insurance status and cancer stage at diagnosis and survival 3 . They found worse short‐ and long‐term survival outcomes for patients without insurance for each stage for all cancers combined.…”
Section: Meeting the Needs Of Cancer Survivorsmentioning
confidence: 99%